Human dignity, human rights, and social justice a Chinese interdisciplinary dialogue with global perspective - Xie, Zhibin 1970-; Kollontai, Pauline; Kim, Sebastian C. H. 1955- (Springer, 2020)
This book explores human dignity, human rights and social justice based on a Chinese interdisciplinary dialogue and global perspectives. In the Chinese and other global contexts today, social justice has been a significant topic among many disciplines and we believe it is an appropriate topic for philosophers, theologians, legal scholars, and social scientists to sit together, discuss, enrich each other, and then deepen our understanding of the topic. Many of them are concerned with the conjuncture between social justice, human rights, and human dignity.
Keywords: Soziale Gerechtigkeit; Menschenwürde; Menschenrecht; China; Dignity; Human rights; Social justice; Political science / Philosophy; Religion and sociology; Aufsatzsammlung